Análise experimental da sensibilidade da tecnologia ultrassônica para medição de gás de queima sob o efeito de curva - Lima, Eric Simão Martins Lima (2013)
This work addresses the upstream bend effects in flow measurement of burning gas systems (flare) simulated by an atmospheric wind tunnel. The similarities between the flare systems and the wind tunnel flows, as well as the introduction to these flow measurements are also presented.The tests were performed with 105 Reynolds (turbulent flow) in tubes with typical upstream fittings configurations used in oil and gas industry. The results were compared with results obtained from numerical simulation noted in the bibliography